The psychedelic renaissance: a case of outlaw user innovation in the pharmaceutical industry. (7th March 2023) - Söderberg, Johan
Abstract : Psychedelic substances are undergoing a renaissance. As they have been out-of-bounds for public research for half a century, the development process has been driven by drug user communities. With the prospect of a legalization of psychedelics, the data collected by users about toxicity, dosage, etc. have been turned into billion-dollar assets. Know-how stemming from stigmatized user communities is being transferred to companies and put under the protection of patent law. This transfer of information is predicated on psychedelics being reframed as therapeutic. The psychedelic renaissance provides an entry point for reflecting in a more critical vein about 'user innovation'.